QUALITY EVALUATION OF DRIED NOODLE WITH SEAWEEDS PUREE SUBSITUTION - Eko Nurcahya Dewi (JOURNAL OF COASTAL DEVELOPMENT, 2011)
The objective of this study was to compare dried noodles made of different type of seaweeds puree and then were compared to noodle which was made without any seaweeds puree subsitution. Different seaweeds puree (E.cottoniii, G. verucossa and mixed beetween them) were subsituted in proportion of 30% in the noodles. The results showed that subsitution of seaweeds puree increased the moisture, crude fiber, ash and iodine content of dried noodles compared to noodle without seaweed puree. The moisture contents : 10.08 ± 2.02 to 13.94% ± 0.84, fat 1.26 ± 0.22 to 2.49 ± 0.81%, crude fiber 2.00 ± 0.4 to 2.25% ± 0.18 and carbohydrate contents 63.37 ± 3.8 to 68.47 % ± 1.5. Iodine concentration in dried noodle with seaweed substitution about 1.06 ± 2.80 to 1.43 ± 0.76 ug/g, protein content 11.84 ± 1.03 to 12.42 ± 0.40 and the carbohydrate content 63.37 ± 3.80 to 68.47 ± 1.59. Significantly tensile strength (p<0.05) were found between the treatments of dried noodles. Higher water absorption by the seaweed lead to softer and spongier textural intensities in the noodles. However, different pattern was observed in the protein and carbohydrate content. The subsitution of different seaweeds puree did not give any significant influence (p>0.05) only for to the taste and colour of dried noodles.